A Change of Pastors ... and How it Affects Change in the Congregation - Mead, Loren B. (Rowman & Littlefield Publishers, 2012)
Twenty years after Critical Moment of Ministry was first published, Loren Mead returns to his groundbreaking work on one of the most important times in a congregation’s life—the time between one pastor’s leaving and another’s arrival. In this revised edition, A Change of Pastors, Mead shares the wisdom he gained from 35 years of studying congregations, wisdom that he hopes will allow congregations to take full advantage of this “extraordinarily pregnant moment” during which incredible congregational change can happen.